Violencia intrafamiliar y los problemas de conductas en estudiantes del octavo año de educación básica de la unidad educativa Babahoyo del cantón Babahoyo. - Cuadro Ortega, Celia Marina (2018)
The objective of the present investigation was to determine the types of intrafamily violence with behavioral problems that take place in the 8th year of the Babahoyo Educational Unit of the Babahoyo canton, in order to carry out this project, we worked with 90 students. The aforementioned sample was given a questionnaire on intrafamily violence and an observation form to detect the types of intrafamily violence and the behavioral problems presented by the students. After the analysis it was determined that 56% the 50 students are victims of psychological violence, 42% (38 students) physical violence, 2% (2 students) sexual violence. In this way, based on the aforementioned studies and the results of the research, it is determined that the development of a training plan in social skills is vital to the students who are victims of intrafamily violence and to those who present behavioral problems. It is also very important that the Institution and the Department of Student Counseling (DECE) know and implement the protocol of action in cases of peer violence detected in the educational institution.